Supervisory transparency in the European banking union - Christopher Gandrud; Mark Hallerberg (Bruegel, 2014)
Bank supervisors should provide publicly accessible, timely and consistent data on the banks under their jurisdiction. Such transparency increases democratic accountability and leads to greater market efficiency. There is greater supervisory transparency in the United States compared to the member states of the European Union. The US supervisors publish data quarterly and update fairly detailed information on bank balance sheets within a week. By contrast, based on an attempt to locate similar data in every EU country, in only 11 member states is this data at least partially available from supervisors, and in no member state is the level of transparency as high as in the US. Current and planned European Union requirements on bank transparency are either insufficient or could be easily sidestepped by supervisors. A banking union in Europe needs to include requirements for greater supervisory transparency.
Keywords: 330; Bankenaufsicht; Bankenregulierung; Bankenliquidität; Bankenstatistik; USA; EU-Mitgliedschaft